TRIGLYCERIDE COMPOSITION OF SIXTEEN STRAINS OF MARINE DIATOM - Lily M.G. Panggabean; Abdullah Rasyid; Zarrah Duniani; Yana Meliana; Indah Kurniasih (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2013)
Trigliceride or triacylglicerol (TAG) composition in crude oil of sixteen strain of marine diatom has been detected by spectra analyses on an Electrospray - Ion Trap – Mass Spectrometry (ESI-IT-MS) HCT Bruker-Daltonic GmbH instrument with AgNO3 used as coordination ionization agent. Biomass samples of each microalga strain were taken from early and late stationary cultures in f/2 enriched seawater and algal oils were extracted according to Bligh and Dyer. Results from spectra analysis showed that P-Pt-P (C16:0-C16:1-C16:0) were distinguished in TAG from diatom strains Chaetoceros sp.1, Chaetoceros sp.2, Thalasiossira sp.1, Thalasiossira sp.2, Thalasiossira sp.3, Navicula sp. 1, Navicula sp. 2, Navicula sp. 3, Navicula sp. 4, Nitzschia sp. 2 and Amphora sp. In contrast, TAGs in Melosira sp. included P-P-P (C16:0-C16:0-C16:0) and P-P-O (C16:0-C16:0-C18:1) were identified. TAGs from Chaetoceros sp. were the most varies among samples, i.e. P-Pt-P (C16:0-C16:1-C16:0), A-P-M (C20:4-C16:0-C14:0), P-Pt-Lt (C16:0-C16:1-C18:3), P-Pt-A (C16:0-C16:1-C20:4), D-P-P (C22:6-C16:0-C16:0), A-Ln-P (C20:4-C18:2-C16:0). Various TAGs were also detected in Nitzschia sp.2, i.e. P-Pt-M (C16:0-C16:1-C14:0), P-Pt-P (C16:0-C16:1-C16:0), P-Pt-S (C16:0-C16:1-C18:0), P-Pt-A (C16:0-C16:1-C20:4). TAGs composition in Skeletonema strains that similar to those in Nitzschia sp.1 has longer carbon, i.e. P-P-O (C16:0-C16:0-C18:1), P-O-O (C16:0-C18:1-C18:1) and O-O-O (C18:1-C18:1-C18:1). TAGs with longer carbon chain and more double bond including highly unsaturated fatty acid C20:4 were increased with culture age in diatoms Chaetoceros sp.1, Chaetoceros sp.2, Thalasiossira sp.2, Navicula sp.1 and Nitzschia sp. 2.Keywords: diatom, TAG, ESI-IT-MS, f/2, early and late stationary